Minimalizowanie zachowań ryzykownych młodzieży oraz wspieranie czynników chroniących w świetle teorii resilience = Minimazing risky behaviours of young people and supporting protective factors in the light of resilience theory - Wawryk, Joanna; Gwozda, Mariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper deals with one of the preventive concepts - resilience. The authors start with terminological assumptions, and then they characterize basic concept areas - risk factors (characterization of risk areas) and protective factors (the authors refer to the conditions enhancing human immunity). The article presents basic information about the resilience concept which is worth referring to while analyzing the causes and mechanisms of behaviour disorders or the symptoms of social maladjustment in children and adolescents.
Keywords: resilience; zaburzenia zachowania; niedostosowanie społeczne; dzieci i młodzież